Analisis Pengaruh Kinerja Keuangan Dan Corporate Social Responsibility Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Kurnianto, Arif; , Imronudin, S.E, M.Si, Ph.D (2017)
effect of financial performance to the value of the firm (study empirical is manufacturing companies listed in Indonesia Stock Exchange). Sampling method that is used is purposive sampling and there are 54 sample companies that will be research objects. Analytical techniques used in this research is multiple linear regression analysis by using SPSS where the data was tested using the coefficient of determination, test F, t test of the significant level is 5%. Furthermore the data was tested using the classical assumptions in terms of The independence variables in this research are financial performance in terms of normality test, multikolinearitas test and heterokedastisitas test. Return On Assets (ROA), Return On Equity (ROE), Operating Profit Margin (OPM), Net Profit Margin (NPM), dan Corporate Social Responsibility (CSR), while the value of the firm as dependent variable. The results of this research show that partially, Return On Assets (ROA), Return On Equity (ROE), Operating Profit Margin (OPM), and Corporat Social Responsibility (CSR) had positive effect and significant to the value of the firm (PBV), while Net Profit Margin (NPM) had negative effect and significant to the value of the firm (PBV).